Systematic review of the diagnostic role of neutrophil to lymphocyte ratio in sarcoidosis: NLR and sarcoidosis - Ghasempour Alamdari, Masoumeh; Kalami, Niusha; Shojaan, Horieh; Aminizadeh, Sarina; Ghaedi, Arshin; Bazrgar, Aida; Khanzadeh, Shokoufeh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: To outline the observations of studies evaluating the prominence of Neutrophil to Lymphocyte Ratio (NLR) in sarcoidosis. Methods: The search was performed on PubMed, Scopus, and web of science up until November 21, 2021. Eventually, a number of 17 papers were incorporated into this review. Results: The results of this analysis showed no significant difference of NLR values between sarcoidosis patients and tuberculosis patients (SMD=-0.36, 95% CI= -0.92-0.21). The results showed high heterogeneity (I2=90.83%, p<0.001). So, we used random-effects model. However, NLR can be utilized to identify the radiological severity and staging of pulmonary sarcoidosis due to statistically significant variations. An elevation in NLR values may assist both sarcoidosis diagnosis and lung parenchyma involvement. Also, extra-pulmonary involvement was just more probable to be found in individuals diagnosed with sarcoidosis inhibiting high rates of NLR. High NLR levels were found to be associated with an accelerated rate of progression, revealing that NLR might be used to detect Pulmonary Hypertension (PH) as a complication of sarcoidosis. Conclusions: In the visualizations of the disease, NLR was revealed to be a beneficial and straightforward fundamental laboratory biomarker connected to disease severity and requirement for therapy.